PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN MASYARAKAT DI DESA PASIRMAE KECAMATAN CIPEUCANG KABUPATEN PANDEGLANG - Dori Aditya; Yaya Sukarya; Temmy Setiawan (MANTRA (Jurnal Manajemen Strategis), 2026)
The Effect of Service Quality and Facilities on Community Satisfaction in Pasirmae Village, Cipeucang District, Pandeglang Regency. This study analyses the effect of service quality and facilities on community satisfaction in Pasirmae Village. Using a quantitative census of 53 respondents and multiple linear regression, the results show that service quality and facilities have positive and significant partial and simultaneous effects. Facilities are the dominant factor, indicating that improving service infrastructure is crucial for increasing community satisfaction